A retrospective analysis of the prevalence of dental diseases in patients with digestive system cancers. Issue 13 (March 2019) - Sakai, Hironori; Yamada, Shin-Ichi; Gibo, Takahiko; Yoshimura, Nobuhiko; Nishimaki, Fumihiro; Kondo, Eiji; Kamata, Takahiro; Kurita, Hiroshi
Abstract : Abstract: The relationship between dental diseases and the prevalence of digestive system cancers remains unclear. The aim of the present study was to examine the prevalence of dental diseases in patients treated for digestive system cancers. The medical and dental records of patients treated for digestive system cancers were retrospectively reviewed, and the results obtained (decayed/filled/missing teeth [DMFT] indices and community periodontal index [CPI] codes) were compared with data from the national survey of dental diseases in order to investigate the relationship between oral health and digestive system cancers. DMFT, D, and F indices were significantly lower, while the M index was slightly higher in digestive system cancer patients than in the national survey. The proportions of individuals with more than 20 residual teeth and denture wearers were significantly lower in cancer patients than in the national survey. The prevalence of periodontitis (CPI codes 3 and 4) and severe periodontitis (CPI code 4) were significantly higher in cancer patients than in the national survey. The present results showed that digestive system cancers were closely associated with multi-tooth loss and/or a low denture-wearing rate. The prevalence of severe periodontitis was also found to be higher in cancer patients. These results suggest that periodontitis and associated multi-tooth loss play a potential role in digestive system cancers. Abstract : Supplemental Digital Content is available in the text